Pain treating neoplastic diseases - Cabieses Molina, Fernando (1956)
The various mechanisms of pain production by neoplasms according to their location and extent arises. A systematic study of patients sore oriented evolution of each case to appropriate therapy, summarized in a "BLADE PAIN" type is presented. The need to employ in an orderly and logical analgesics, indicating a working method in the Service who work arises. Technique, indications and contradictions of the various types of analgesic use more surgery is considered. Recordada- necessity, not always directly treat the culprit lesion pain, with the means available to the oncologist, using analgesia by various means discussed in the thesis, in addition to surgery, radiation is stressed, or hormone therapy, etc. It emphasizes the need to alleviate the pain in the fullest possible way, ensuring minimal damage to the body or the personality of the patient.